Diversity of kidney care referral pathways in national child health systems of 48 European countries - Tasic, Velibor; Edvardsson, Vidar O.; Preka, Evgenia; Prikhodina, Larisa; Stefanidis, Constantinos J.; Topaloglu, Rezan; Shtiza, Diamant; Sarkissian, Ashot; Mueller-Sacherer, Thomas; Fataliyeva, Rena; Kazyra, Ina; Levtchenko, Elena; et al. (Frontiers in Pediatrics, 2024)
Background Primary, secondary and tertiary healthcare services in Europe create complex networks covering pediatric subspecialties, sociology, economics and politics. Two surveys of the European Society for Paediatric Nephrology (ESPN) in 1998 and 2017 revealed substantial disparities of kidney care among European countries. The purpose of the third ESPN survey is to further identify national differences in the conceptualization and organization of European pediatric kidney health care pathways during and outside normal working hours. Methods In 2020, a questionnaire was sent to one leading pediatric nephrologist from 48 of 53 European countries as defined by the World Health Organization. In order to exemplify care pathways in pediatric primary care nephrology, urinary tract infection (UTI) was chosen. Steroid sensitive nephrotic syndrome (SSNS) was chosen for pediatric rare disease nephrology and acute kidney injury (AKI) was analyzed for pediatric emergency nephrology. Results The care pathways for European children and young people with urinary tract infections were variable and differed during standard working hours and also during night-time and weekends. During daytime, UTI care pathways included six different types of care givers. There was a shift from primary care services outside standard working hours to general outpatient polyclinic and hospital services. Children with SNSS were followed up by pediatric nephrologists in hospitals in 69% of countries. Patients presenting with community acquired AKI were admitted during regular working hours to secondary or tertiary care hospitals. During nights and weekends, an immediate shift to University Children's Hospitals was observed where treatment was started by intensive care pediatricians and pediatric nephrologists. Conclusion Gaps and fragmentation of pediatric health services may lead to the risk of delayed or inadequate referral of European children with kidney disease to pediatric nephrologists. The diversity of patient pathways outside of normal working hours was identified as one of the major weaknesses in the service chain.